Efektivitas Bimbingan Belajar terhadap Kesulitan Belajar Siswa Kelas XII MA Muallimin NW Gunung Rajak Tahun Pelajaran 2018/2019 - Ahmad Izzuddin (MANAZHIM, 2019)
This study aims to determine the effectiveness of tutoring on learning difficulties of students of class XII MA Muallimin NW Gunung Rajak. The subjects that are the focus of research are Chemistry subjects. This research is a quantitative research with experimental design. The subject of this study was students of class XII IPA MA Muallimin NW Gunung Rajak. Data collection techniques using questionnaires, documentation, interviews, and observations. The implementation of tutoring given to students who have effective learning difficulties in improving learning outcomes of students of class XII IPA MA Muallimin NW Gunung Rajak in the academic year 2018/2019. This can be seen from the acquisition of values ​​in statistical analysis of 3.991. This value is greater than the value of ttable at the significance level of 5% which is equal to 1.658 and at the 1% significance level of 2.358. Therefore, the implementation of tutoring is effective in overcoming student learning difficulties, especially in Chemistry subjects.